VALIDITAS E-MODUL KIMIA SMA KELAS XI BERBASIS PROBLEM BASED LEARNING PADA MATERI LAJU REAKSI FASE F - Indah Annisa Fitri; Iryani Iryani (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
Reaction rate material is material that requires visualization that can realistically depict events and factors that influence reaction rates, and requires conceptual understanding and mathematical operation skills. Therefore, teaching materials are needed that can increase students' understanding by using e-modules. This research aims to determine the validity category of e-modules based on problem based learning on class XI F phase reaction rate material. This research is Educational Design Research (EDR) which uses the plomp model consisting of 3 stages, namely preliminary research, prototyping and assessment, but this research is limited to prototype stage III, namely e-module validation. The research subjects were UNP chemistry lecturers and chemistry teachers as validators. Validation of the e-module uses an instrument in the form of a validity questionnaire consisting of content validity and construct validity which includes presentation, language and graphics. Validation was carried out by 5 validators, consisting of 3 chemistry lecturers and 2 chemistry teachers. The results were analyzed using Content Validity Ratio (CVR) for content validity and Aiken's V formula for construct validity. The results of the validity analysis revealed an average content validity value of 1.00 and construct validity with an average V value of 0.87. The results of the content and construct validity values of the e-module show that the e-module produced is in the valid category.